Level of Awareness and Utilization of Sexual and Reproductive Health Services among Adolescents in Secondary Schools in Turkana South Sub-County, Turkana County, Kenya - Lobolia, Abong William; M’mayi, Consolata; Kyulu, Teresia (International Journal of Professional Practice, 2024)
Adolescence is a time when teenagers exhibit rapid growth and development that is mainly characterized by emotional, sexual, cognitive, and physical changes. Therefore, when attention is accorded to enlighten them on these changes, they are able to cope amicably. However, there has been persistent reproductive health problems among adolescent secondary school students. The purpose of the study was to examine the level of awareness and utilization of sexual and reproductive health services among adolescents in secondary schools in Turkana South Sub-County, Turkana County, Kenya. The study used descriptive cross-sectional design. The target population was 2,748 male and female adolescents aged 15-19 years attending 14 secondary schools in Turkana South Sub County. Simple random sampling method was used to select 337 respondents, who answered to the questionnaire. The sample was between 10-30% of the population as recommended by Mugenda and Mugenda (2003) for a population below 10,000. Pilot test was conducted on 34 adolescents in Loturerei Mixed Day Secondary School in Turkana central. Cronbach alpha coefficient was used to measure reliability, while construct and content validity were ensured. Descriptive statistics such as frequencies and percentages and inferential statistics such as Chi-square were to analyze the data. Results were presented using tables and explanations. Results indicated that most respondents had little or no knowledge of adolescent sexual reproductive health programs, with only 15.58 percent of the 337 respondents acknowledging to be aware of services offered under the program. The study concluded that referrals from trusted sources, including professionals and peers, were highly effective in encouraging healthcare utilization. However, written materials and school noticeboards had limited impact, suggesting the need for more interactive and targeted awareness strategies. The study, therefore recommended a series of comprehensive awareness campaigns to sensitize adolescents on reproductive health programs and services.